Voicing narratives of structural violence in interpersonal firearm violence research and prevention in the United States - Buggs, Shani A.L.; Lund, Julia J.; Kravitz-Wirtz, Nicole (Frontiers in Public Health, 2023)
Violence is defined as “the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community, that either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment, or deprivation.” Encompassed in this definition are multiple, interrelated forms of violence, including interpersonal firearm death and injury, but also the systems, policies, and practices enacted by those with power to advantage some groups while depriving others of meaningful opportunities for meeting their basic needs—known as ‘structural violence’. Yet dominant violence prevention narratives too often ignore or deemphasize the deeply intertwined threads of structural violence with other forms of violence, leading to policies and practices that are frequently insufficient, and often harmful, for reducing interpersonal firearm violence and building community safety, particularly in minoritized and structurally marginalized communities. We highlight ways in which limited scrutiny of structural violence, the omission of its defining characteristics—power and deprivation—from functional characterizations and frameworks of interpersonal firearm violence, and the inadequate distribution of power and resources to those most impacted by violence to self-determine narratives of and solutions to this issue, grossly impacts how interpersonal firearm violence is collectively conceived, discussed, and addressed. Expanding dominant narratives of interpersonal firearm violence such that the goal of prevention and intervention efforts is not merely the absence of violence but rather the creation of a community safety and health ecosystem, is essential to meet this critical moment in firearm violence research and prevention.